2014
DOI: 10.1073/pnas.1403521111
|View full text |Cite
|
Sign up to set email alerts
|

Extensive pathogenicity of mitochondrial heteroplasmy in healthy human individuals

Abstract: A majority of mitochondrial DNA (mtDNA) mutations reported to be implicated in diseases are heteroplasmic, a status with coexisting mtDNA variants in a single cell. Quantifying the prevalence of mitochondrial heteroplasmy and its pathogenic effect in healthy individuals could further our understanding of its possible roles in various diseases. A total of 1,085 human individuals from 14 global populations have been sequenced by the 1000 Genomes Project to a mean coverage of ∼2,000× on mtDNA. Using a combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

33
228
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(265 citation statements)
references
References 44 publications
33
228
3
1
Order By: Relevance
“…4B). The higher hN/hS ratio is in keeping with previous observations, and probably reflects negative selection against some NS heteroplasmies that prevents them from reaching "fixation" within an individual, and thereby appearing as polymorphisms (2,4). Surprisingly, the hN/hS ratio for TSHs in the liver is 3.11 ( Fig.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…4B). The higher hN/hS ratio is in keeping with previous observations, and probably reflects negative selection against some NS heteroplasmies that prevents them from reaching "fixation" within an individual, and thereby appearing as polymorphisms (2,4). Surprisingly, the hN/hS ratio for TSHs in the liver is 3.11 ( Fig.…”
Section: Resultssupporting
confidence: 89%
“…In addition, we find a significantly elevated hN/hS ratio in liver tissue. These results indicate that positive selection, in addition to drift and negative selection (2,4,14,25), plays a major role in influencing human mtDNA heteroplasmies. Some of the HFH alleles that we identify are also associated with tumors of specific tissues (SI Appendix, Table S2); whether this association simply reflects the increased frequency of that allele in that tissue during aging, or whether the HFH plays a role in causing the tumor, remains an open question.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Within the spectrum of mitochondrial diseases, the onset of symptoms can vary according to Copyright © 2016 Apart from the occurrence of pathogenic mtDNA variants, naturally occurring variants have also been reported in humans (Li et al 2010;Goto et al 2011;Payne et al 2013), which also have the potential to affect the health of the individual and lead to disease (Kirches et al 2001;Coon et al 2006;He et al 2010;Ye et al 2014). A recent study has shown the effect of maternal age on heteroplasmic transmission between the mother and child (Rebolledo-Jaramillo et al 2014).…”
mentioning
confidence: 99%